Farrerol Attenuates Cisplatin-Induced Nephrotoxicity by Inhibiting the Reactive Oxygen Species-Mediated Oxidation, Inflammation, and Apoptotic Signaling Pathways - Ma, Ning; Wei, Wei; Fan, Xiaoye; Ci, Xinxin (Frontiers in Physiology, 2019)
Cisplatin is a chemotherapy drug that is often used in clinical practice, but its frequent use often leads to nephrotoxicity. Therefore, we urgently need a drug that reduces the nephrotoxicity induced by cisplatin. Farrerol reportedly has antioxidant potential, but its renal protective effects and potential mechanisms remain unclear. In this study, we used both cell and mouse models to determine the mechanism of farrerol in cisplatin-induced nephrotoxicity. The in vitro experiments revealed that farrerol improved cisplatin-induced nephrotoxicity and reactive oxygen species (ROS) production via nuclear factor erythrocyte 2-related factor 2 (Nrf2) activation. Moreover, farrerol effectively activated Nrf2 and subsequently increased the expression of Nrf2-targeted antioxidant enzymes, including heme oxygenase-1 (HO-1) and NAD(P)H quinone oxidoreductase-1 (NQO1), but inhibited Kelch-like ECH-associated protein 1 (Keap1) and NADPH oxidase type 4 (NOX4). Furthermore, farrerol attenuated the phosphorylation of C-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (p38), the activation of phosphorylated nuclear factor-κB (p-NF-κB) and nucleotide-binding domain (NOD)-like receptor protein 3 (NLRP3), and the expression of phosphorylated p53 (p-p53), Bax and cleaved caspase-3. In vivo, farrerol significantly improved cisplatin-induced renal damage, as demonstrated by the recovery of blood urea nitrogen (BUN), serum creatinine (SCr), kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL) and pathological damage. Moreover, farrerol inhibited inflammatory and apoptotic protein expression in vivo. Notably, farrerol exerted slight protection in Nrf2-knockout mice compared with wild-type mice. These findings indicate that farrerol can effectively activate Nrf2 and can serve as a therapeutic target in the treatment of acute kidney injury (AKI).